2020
DOI: 10.1007/s00402-020-03348-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, diagnostics and treatment algorithm of nerve lesions after traumatic shoulder dislocations: a retrospective multicenter study

Abstract: Background The shoulder is the joint most prone to dislocating in the human body and accounts for 45% of all dislocations. In addition to ruptures of the soft tissue and bony injuries, lesions to vascular structures as well as the brachial plexus and its corresponding nerves might occur. With an incidence of up to 65%, nerve lesions are frequently reported after shoulder dislocations. The aim of this study is to obtain information on epidemiology, diagnostics, treatment and duration until remission or late seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
1
15
0
2
Order By: Relevance
“…Patients' clinical outcomes were classified as no impairment (subjectively satisfied, no problems in activities of daily living (ADLs)), mild impairment (subjectively not satisfied, no problems with ADLs), and impairment (subjectively not satisfied, problems with ADLs) [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' clinical outcomes were classified as no impairment (subjectively satisfied, no problems in activities of daily living (ADLs)), mild impairment (subjectively not satisfied, no problems with ADLs), and impairment (subjectively not satisfied, problems with ADLs) [2].…”
Section: Methodsmentioning
confidence: 99%
“…The brachial plexus and its branches originate from the cervical spine, pass through the shoulder girdle, and run through the entire upper extremity [1]. The glenohumeral joint of the shoulder is a shallow ball and socket joint and is the joint with the highest mobility in the human body [2]. Shoulder trauma can cause various types of injury, such as glenohumeral joint dislocation, acromioclavicular joint injury, humeral fracture, clavicular fracture, and soft tissue injury, including rotator cuff tear [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In a review of inferior dislocations, the proportion of nerve injuries was higher: 59% of the 80 cases had some degree of nerve injury 16 , the axillary nerve most commonly affected. In a multicenter study on nerve lesions after shoulder dislocations, Tiefenboeck et al found that the direction of dislocation, anterior, posterior, or inferior, did not appear to influence the rate of nerve injuries 31 . Interestingly though, in their case series of patients with nerve injuries after shoulder dislocation inferior dislocation was much more prevalent (17%) than normally would be expected 31 .…”
Section: Nerve Injuriesmentioning
confidence: 99%
“…In a multicenter study on nerve lesions after shoulder dislocations, Tiefenboeck et al found that the direction of dislocation, anterior, posterior, or inferior, did not appear to influence the rate of nerve injuries 31 . Interestingly though, in their case series of patients with nerve injuries after shoulder dislocation inferior dislocation was much more prevalent (17%) than normally would be expected 31 . In our series of 27 patients, 11 had clinical signs of nerve injury, which was found to be transient in all cases (Table 3).…”
Section: Nerve Injuriesmentioning
confidence: 99%
“…Most patients recover spontaneously within one year and regain muscle strength and sensation, but range of motion may be slightly limited in the injured shoulder 17. Less than 1% of patients have persistent brachial plexus and peripheral nerve injuries beyond one year, according to a retrospective multicentre study (15 739 patients) 19…”
Section: What Complications Are Associated With Shoulder Dislocation?mentioning
confidence: 99%